Debt patterns of the peripheral economies of Europe: from the increased growth post-implementation of the Euro to the Great Recession - Barbant, Yasmim Dalila; Souza, Leonardo Flauzino de (Brazilian Keynesian Review, 2019)
The main purpose of this article is to outline the specificities of the indebtedness process of each country of the European periphery — Greece, Italy, Ireland, Portugal, and Spain — that guided the behavior of the demand and the indebtedness of the domestic economic agents from 2000 to 2017. The main results indicated that from 2000 to 2008, all of the countries had foreign sector surpluses (current account deficits), which characterized distinct indebtedness processes of the domestic economic agents. The reversal of these processes was accompanied by larger public deficits and the replacement of private debt with public debt. With the exception of Ireland, the positive impacts on the economic performance of these countries between 2009 and 2017 came from the foreign sector through the devaluation of the euro in the period.